Figure 2 from: Svensson M, Ekman S, Klepsland JT, Nordin A, Thor G, von Hirschheydt G, Jonsson F, Knutsson T, Lif M, Spribille T, Westberg M (2017) Taxonomic novelties and new records of Fennoscandian crustose lichens. MycoKeys 25: 51-86. https://doi.org/10.3897/mycokeys.25.13375 - Svensson, Måns; Ekman, Stefan; Klepsland, Jon T.; Nordin, Anders; Thor, Göran; von Hirschheydt, Gesa; Jonsson, Fredrik; Knutsson, Tommy; Lif, Mattias; Spribille, Toby; Westberg, Martin (Zenodo, 2017)
Figure 2 - A Catillaria scotinodes (UPS L-785594) B Gyalidea subscutellaris (UPS L-679028) C Micarea hylocomii (UPS L-803526) D Micarea lynceola (UPS L-778164). Scale bars: 0.5 mm.